A mobile solution to help visually impaired people in public transports and in pedestrian walks - Brito, D. (2022)
Promoting social inclusion is a field of active research and an emergent topic that relates to blind and visually impaired people. They face plenty of problems in their daily routines and solutions to increase their independence are important. Among the difficulties they face, we discuss two that aim to help them in the use of public transport and the carrying out of walking routes between strategic points such as the City Hall, Finances, Health Center, etc. While the first task can be easier to accomplish, the later relies on GPS and as there are places with week signal, there are some additional difficulties. In this paper, we present a case study, developed in the Historical Center of Viana do Castelo, a city on the north of Portugal, which had the collaboration of a Visually Impaired Association that helped us along the process of the mobile application development and field tests. We present the objectives, developed prototypes, performed tests and evaluation of the system. ? 2018 WIT Press.